Daytime rest: Association with 24‐h rest–activity cycles, circadian timing and cognition in older adults. Issue 3 (7th August 2022) - Reyt, Mathilde; Deantoni, Michele; Baillet, Marion; Lesoinne, Alexia; Laloux, Sophie; Lambot, Eric; Demeuse, Justine; Calaprice, Chiara; LeGoff, Caroline; Collette, Fabienne; Vandewalle, Gilles; Maquet, Pierre; et al.
Abstract: Growing epidemiological evidence points toward an association between fragmented 24‐h rest–activity cycles and cognition in the aged. Alterations in the circadian timing system might at least partially account for these observations. Here, we tested whether daytime rest (DTR) is associated with changes in concomitant 24‐h rest probability profiles, circadian timing and neurobehavioural outcomes in healthy older adults. Sixty‐three individuals (59–82 years) underwent field actigraphy monitoring, in‐lab dim light melatonin onset assessment and an extensive cognitive test battery. Actimetry recordings were used to measure DTR frequency, duration and timing and to extract 24‐h rest probability profiles. As expected, increasing DTR frequency was associated not only with higher rest probabilities during the day, but also with lower rest probabilities during the night, suggesting more fragmented night‐time rest. Higher DTR frequency was also associated with lower episodic memory performance. Moreover, later DTR timing went along with an advanced circadian phase as well as with an altered phase angle of entrainment between the rest–activity cycle and circadian phase. Our results suggest that different DTR characteristics, as reflective indices of wake fragmentation, are not only underlined by functional consequences on cognition, but also by circadian alteration in the aged.